KONTRIBUSI MOTIVASI BELAJAR DAN KOMPETENSI KEPRIBADIAN GURU TEHADAP HASIL BELAJAR KETERAMPILAN KOMPUTER DAN PENGELOLAAN INFORMASI SISWA KELAS XI TEKNIK KOMPUTER JARINGAN SMK NEGERI TAMAN FAJAR PEUREULAK - Ridwan Miaria; Nelda Azhar; Legiman Slamet (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
This study aims to reveal the contribution of learning motivation and competence of the teacher's personality on learning outcomes computer skills and information management SMKN Taman Fajar Peueulak. The hypothesis is: (1) learning motivation and competence of the teacher's personality together contribute significantly to the learning outcomes, (2) learning motivation contribute significantly to the learning outcomes and (3) Competence of teachers‘s personality contribute significantly to the learning outcomes. This research is classified in the study associative correlation. The data study outcome variables is from KKPI teacher and learning motivation and competence of the teacher's personality collected through questionnaires distributed to students by using a Likert scale and  has been tested for validity and reliability. Data is considered to have met the assumptions and requirements analysis; normal distribution of data, linear pattern, the data is homogeneous and there is no multicollinearity problem. The population was all students of class XI Computer Network Engineering in the academic year 2014/2015 with sampling using Taro Yamane formula involving 41 samples from 68 populations of students of class XI Computer Network Engineering of TKJ I and II. The results of data analysis showed: (1) learning motivation contribute to the learning outcomes of 10.17%, (2) competence of teachers personality contribute to the learning outcomes of 17.05%, and (3) learning motivation and competence of the teacher's personality contribute together  to the learning outcomes of 36.00%. The findings of this study is learning motivation  and competence of the teacher's personality are factors that influence student learning outcomes. However, of course there are other factors that also affect student learning outcomes. Keywords : Learning motivation, competence of the teacher's personality and computer skills and                    information management